2020
DOI: 10.1007/s10708-020-10260-x
|View full text |Cite
|
Sign up to set email alerts
|

Verifying Indigenous based-claims to forest rights using image interpretation and spatial analysis: a case study in Gunung Lumut Protection Forest, East Kalimantan, Indonesia

Abstract: The decision of Indonesian's constitutional court in May 2013, to review Law Number 41/1999 on Forestry, marked a significant step forward in Indonesian policy related to recognition of the rights of Indigenous people to forest. Under the decision, Indigenous forest is no longer considered State forest and rights to it should be granted to Indigenous communities inhabiting them as long as there is proof of their Indigenous status. However, at the implementation level, special measures are required to ascertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…From their research on the Dayak Paser indigenous community in East Kalimantan, Nugroho et al [64] found that there was a change in the behavior of the indigenous people living around the Gunung Lumut protected forest, who had been known to hold and apply the norms, beliefs, and traditional wisdom and knowledge of their ancestors that was due to an increased desire for modern life, better accessibility, and socio-cultural assimilation with immigrant communities. Nugroho et al [64] believe that without efforts to maintain traditional values, a strong relationship with nature, which is often important to the identity of indigenous peoples, will not be able to last much longer. This is based on the real conditions on the ground, where even remote communities are forced by the 'needs of life' to convert their ancestral forests into rubber and oil palm plantations in order to simply survive.…”
Section: Limitations and Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…From their research on the Dayak Paser indigenous community in East Kalimantan, Nugroho et al [64] found that there was a change in the behavior of the indigenous people living around the Gunung Lumut protected forest, who had been known to hold and apply the norms, beliefs, and traditional wisdom and knowledge of their ancestors that was due to an increased desire for modern life, better accessibility, and socio-cultural assimilation with immigrant communities. Nugroho et al [64] believe that without efforts to maintain traditional values, a strong relationship with nature, which is often important to the identity of indigenous peoples, will not be able to last much longer. This is based on the real conditions on the ground, where even remote communities are forced by the 'needs of life' to convert their ancestral forests into rubber and oil palm plantations in order to simply survive.…”
Section: Limitations and Constraintsmentioning
confidence: 99%
“…Technology and local knowledge can be synergized to become a great force in supporting the management of natural resources that are vulnerable to degradation, such as those in upstream watersheds. On the other hand, scientific knowledge is built based on systematic quantitative technology and methodology, but it is generally weak in terms of long-term experience, which is the main characteristic of TK [64]. In the future, it will be necessary to incorporate TK into sociotechnical measures that are based on science.…”
Section: Incorporating Traditional Knowledge Into Science-based Socio...mentioning
confidence: 99%
“…Similarly, shifting cultivation has been investigated in Sumatra, such as in Kerinci Seblat National Park (Hariyadi & Ticktin, 2012) and Lampung (Syam et al, 1997), but different in Borneo. Therefore, most of the studies of shifting cultivation are concentrated in Kalimantan and Sumatra, with a focus on land use change (Nugroho et al, 2018), socio cultural (Nugroho et al, 2020), policy and governance (Thaler & Anandi, 2017), as well as biodiversity (Takeuchi et al, 2019).…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…Within an international perspective, there has been no formal definition of Indigenous peoples in the United Nations system (Asia Pacific Forum of National Human Rights Institutions and the Office of the United Nations High Commissioner for Human Rights [APF and OHCHR], 2013: 6;Cobo, 2004). One of the alternate descriptions of tribes is Indigenous people (Errico, 2017;Nugroho et al, 2020). However, one of the most cited descriptions of the concept of the Indigenous peoples was offered by Jose Martinez Cobo (2004):…”
Section: Introductionmentioning
confidence: 99%
“…Within an international perspective, there has been no formal definition of Indigenous peoples in the United Nations system (Asia Pacific Forum of National Human Rights Institutions and the Office of the United Nations High Commissioner for Human Rights [APF and OHCHR], 2013: 6; Cobo, 2004). One of the alternate descriptions of tribes is Indigenous people (Errico, 2017; Nugroho et al, 2020). However, one of the most cited descriptions of the concept of the Indigenous peoples was offered by Jose Martinez Cobo (2004): Indigenous communities, peoples and nations are those which, having a historical continuity with pre-invasion and pre-colonial societies that developed on their territories, consider themselves distinct from other sectors of the societies now prevailing in those territories, or parts of them.…”
Section: Introductionmentioning
confidence: 99%